Utility of Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Patients with Fever of Unknown Origin Diagnosed as Lymphoma - Sheng, Zi-Ke (Med Princ Pract, 2014)
OBJECTIVE: To assess the efficacy of fluorine-18 fluorodeoxyglucose positron emission tomography ((18)F-FDG PET)/computed tomography (CT) in the diagnosis of patients with fever of unknown origin (FUO), who were finally diagnosed as lymphoma. SUBJECTS AND METHODS: A retrospective study was performed in the First Affiliated Hospital, School of Medicine of Zhejiang University, China, from March 2009 to March 2012. The PET/CT images of consecutive patients with FUO were analyzed. Within 1 week of PET/CT scanning, additional histological tests were also performed if clinically needed. RESULTS: A total of 73 consecutive patients were included. Of these, 34 (47s%) had a PET/CT finding suggestive of the presence of lymphoma and 29 (85s%) had a diagnosis of confirmed lymphoma; 39 (53s%) had a PET/CT result revealing the absence of lymphoma and 4 (10s%) were diagnosed by biopsy as having lymphoma. The most frequent lymphoma diagnosis was peripheral T cell lymphoma (n = 16; 55s%), followed by diffuse large B cell lymphoma (n = 9; 31s%). The accuracy of PET/CT was 88s%. CONCLUSION: In this study, PET/CT had high diagnostic accuracy in patients with FUO resulting from lymphoma, which indicated that PET/CT scanning was a valuable diagnostic tool for these groups of patients with FUO.